T-S Fuzzy Model Design for Engine Torque Control System of Spark Ignition Engine - Triwiyatno, Aris; Nuh, Mohammad; Santoso, Ari; Sutantra, I Nyoman (Transmisi, 2009)
On many occasions, fuzzy rule-based systems have been demonstrated to be powerful tools in modeling, decision making and automatic control. The T-S model approach consists to construct nonlinear or complex dynamic systems that cannot be exactly modeled by mathematical model, by means of interpolating the behavior of several LTI (Linear Time Invariant) sub models. In this paper, a new modification fuzzy model based on T-S model will be designed to represent engine torque control system of spark ignition engine, since spark ignition engine is a high non linear system with wide uncertainties that very difficult to be modeled by mathematical model. Keywords: T-S model, fuzzy model, engine torque, spark ignition engine.